Clinical features and molecular bases of neuroacanthocytosis. - Rampoldi, L; Danek, A; Monaco, A (2002)
The term acanthocytosis is derived from the Greek for "thorn" and is used to describe a peculiar spiky appearance of erythrocytes. Acanthocytosis is found to be associated with at least three hereditary neurological disorders that are generally referred to as neuroacanthocytosis. Abetalipoproteinaemia is an autosomal recessive condition, characterised by absence of serum apolipoprotein B containing lipoproteins leading to fat intolerance and fat-soluble vitamin deficiency. This results in a progressive spinocerebellar ataxia with peripheral neuropathy and retinitis pigmentosa. Chorea-acanthocytosis is also an autosomal recessive condition and is characterised by chorea, orofaciolingual dyskinesia, dysphagia, dysarthria, areflexia, seizures and dementia. Some of its features, including choreic movements, peripheral neuropathy with areflexia, elevated serum creatine kinase levels and myopathy are shared by another form of neuroacanthocytosis, McLeod syndrome. Patients affected by this X-linked disorder also show abnormal expression of Kell blood group antigens and a permanent haemolytic state. In addition to these cases, acanthocytosis is occasionally associated with other neurological disorders, such as Hallervorden-Spatz disease. For each of the neuroacanthocytosis syndromes we review the main clinical features and their molecular bases. The recent molecular genetics findings are the first step towards the understanding of the pathogenetic mechanisms and eventually the search for effective treatments.